PENGENDALIAN PEREDARAN PAKAIAN BEKAS DI KABUPATEN INDRAGIRI HILIR - Afiah, Tamamal; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Control in principle is components in the management process that have an important role in the process of achieving the stated objectives and correcting existing irregularities. Control provides answers to irregularities, problems were found, namely the circulation of used clothing in Indragiri Hilir. The purpose of study is knowing how to control and inhibit the distribution of used clothing in Indragiri Hilir. The theoretical concept used is control measures by Siswanto which consist of: set standards, measure performance, compare performance in accordance with standards, and take corrective action. . The research method used is a type of qualitative by expressing fonomenology, the selection of informants using the purposive sampling adn snawball sampling technique. The techniques of collecting data are through observation, interviews, library studies, and documentation. The results of this study the Department of Trade and Industry as the executor of the policy showed that control was never carried out in controlling the circulation of used clothing in Indragiri Hilir. Keywords: Control, Circulation, Used Clothing